A Comparative Study of Impact of KVKs Managed by Different Agencies in Uttar Pradesh (Indian Journal of Extension Education, 2014)
The Krishi Vigyan Kendra (KVK) provides a strong training support for bringing about production breakthrough in agriculture. Krishi Vigyan Kendras are functional in carrying out extension activities in accordance with government programme schedule and providing support to raise the skill of the farmers which will help them to increase their farm productivity. On the basis of findings and observations of the study, it may be concluded that most of the farmers were having either marginal or small holdings. Majority of the respondents were having farming as their main occupation. The KVK beneficiaries differed significantly in case of knowledge, attitude and skill. New agricultural technologies dissemination through KVK were adopted by the farmers to a considerable extent. Highest adoption was found by the KVK of NGO which may be due to better and adequate infrastructure and other facilities. Among the three selected KVKs, the performance of KVK of the NGO, Sultanpur was found to be superior. Nearly 60 per cent beneficiaries reported that after receiving training from KVK, their farm productivity increased. Forty per cent of the beneficiaries fully adopted recommendations of the KVK, while 40 per cent adopted it partially.